Prevalence of dental anomalies in patients with cleft lip alveolus and palate treated at Institute Specialized on Children’s Health Lima Perú - Mogollón Tello, Luis Alberto (2008)
The Prevalence and distribution of dental anomalies in patients with cleft lip alveolus and palate (CLAP) were studied using panoramic x-rays of 129 children (79 boys and 50 girls), 6 to 12 year old belonging the Institute specialized on Children’s Health, Lima - Perú, during 2005 to 2008. Hypodontia prevalence of 86.8% and supernumerary teeth prevalence in the 49.6% was found in the population. Both anomalies were simultaneously found in 43.4%. The studied population showed 78 patients with unilateral CLAP (60.5%) and 51 with bilateral CLAP (39.5%). According to the relationship between hypodontia distribution and gender, 68 cases (60.7%) were boys and 44 girls (39.3%); whereas in the supernumerary teeth, 42 cases (65.6%) boys and 22 cases were girls (34,4%). Comparing frequency of hypodontia and supernumerary teeth with the type of cleft, the most affected group was the bilateral CLAP group with 48 cases (42.9%) and 27 (42.2%) respectively, whereas the group of unilateral left CLAP was the one which were more affected in both dental anomalies. Hypodontia appeared mainly in the opposed side to the cleft (96,4%) whereas supernumerary teeth are observed generally in the cleft side (92,2%). 41 children shown hypodontia in one tooth (36.6%) and 34 children showed only 2 (30.4%), being more affected the maxillary lateral incisor (92,9%) and maxillary second premolar (38.4%). Most of the patients (60.9%) had 1 supernumerary tooth and 23 patients (35.9%) had 2 supernumerary teeth; placed frequently in between the maxillary lateral incisor and maxillary canine, appearing generally non erupted (79.7%). Most of the supernumerary teeth had a non typical shape.